REGULACIÓN DEL USO PROGRESIVO DE LA FUERZA DEL SERVIDOR MILITAR Y POLICIAL EN EL CUMPLIMIENTO DEL DEBER LEGAL. - RIVERA JIMÉNEZ., KARLA THALÍA (2021)
This research work is entitled "Regulation of the progressive use of force by the military and police servant in the fulfillment of legal duty", which arises from the perspective and analysis carried out both in the Constitution of the Republic of Ecuador in its article 393. That it indicates that human security is guaranteed by the State through guidelines and acts that ensure an environment of peace, free from violence and discrimination, among others; those considering the aspects and regulations of a constitutional, international nature, encompassed by human rights with the issue raised. We will address issues within the present investigation such as the lack of an adequate guarantee regarding the regulation of the progressive use of force by both military and police officers, which has generated the existence of abuses and inappropriate actions by law enforcement agencies as described. Has been able to demonstrate in the latest demonstrations and through the states of exception issued by the state as an example, those that were dictated in October 2019 and during the Covid-19 health crisis in 2020. We will also analyze that a derivation of the problem arises when the laws are not clear and therefore there is a tendency to misinterpretations that lead to the fact that at the time of acting the police or military member abuses their faculty causing serious damage to people, without a doubt It tries to unprotect the servant of the forces of order in their work, but that those people called to use force progressively are educated and prepared 16 for any type of circumstance, that their actions do not involve influences of a political nature, nor do they respond to government leaderships whose purpose is personal but not collective interests. Similarly, Decree No. 179, issued by the Ecuadorian government that regulates the progressive use of force by the armed forces, and its unconstitutionality after its respective analytical study, will be analyzed. When considering a new reform to the Comprehensive Organic Criminal Code that refers to the causes of unlawfulness to police officers and prison guides in reference to article 30.1, on compliance with the legal duty of the National Police and prison security server, That mentions the powers that the aforementioned members have regarding situations in which their duty is to ensure the protection of people's rights, which in turn protects said servers, but that the facts have shown us that they have Valid of said articles to generate a bad fulfillment of the so-called legal duty. Therefore, for the faithful fulfillment of the proposed objectives, I proceeded to make a theoretical, legal and doctrinal conglomerate in addition to an essential part such as comparative legislation and field research in relation to the regulation of the progressive use of force by police members and military in the Republic of Ecuador. In the same way, the application of methods and techniques such as the survey and the interview that was directed towards legal professionals with which I was able to obtain concrete results and criteria, from which clear and concise foundations emerge for the proposal of reforms necessary to solve this problematic. 17 With all the aspects described above and that are studied in this work, which in its final part establishes the approach of a legal proposal according to the current legal reality, aimed at respecting the mandates established in the Magna Carta of our country, Human rights being a fundamental pillar of Ecuadorian citizens, understood as the way to respond to the provisions issued by government authorities that are affected, thus guaranteeing compliance with this right when considering the attribution of a criminal nature with which we ensure a fair resolution where the punitive or sanctioning power, that is, on the part of the justice operators, is respecting the constitutional rights and guarantees.